2007
DOI: 10.1088/0022-3727/40/18/r01
|View full text |Cite
|
Sign up to set email alerts
|

Status and trends of short pulse generation using mode-locked lasers based on advanced quantum-dot active media

Abstract: In this review, the potential of mode-locked lasers based on advanced quantum-dot (QD) active media to generate short optical pulses is analysed. A comprehensive review of experimental and theoretical work on related aspects is provided, including monolithic-cavity mode-locked QD lasers and external-cavity mode-locked QD lasers, as well as mode-locked solid-state and fibre lasers based on QD semiconductor saturable absorber mirrors. Performance comparisons are made for state-of-the-art experiments. Various met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Recently a new generation of mode-locked semiconductor lasers based on quantum dot (QD) material was developed [3]. These lasers demonstrate many advantages over conventional quantum well lasers, such as low threshold current, small alpha factor [4], low pulse chirp, high stability to noise, and external feedback, among others [5,6]. It was recently shown that QD mode-locked lasers can generate very short subpicosecond optical pulses [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new generation of mode-locked semiconductor lasers based on quantum dot (QD) material was developed [3]. These lasers demonstrate many advantages over conventional quantum well lasers, such as low threshold current, small alpha factor [4], low pulse chirp, high stability to noise, and external feedback, among others [5,6]. It was recently shown that QD mode-locked lasers can generate very short subpicosecond optical pulses [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum peak power is 103 mW with a corresponding pulsewidth of 6.5 ps and a time-bandwidth product of 1.88. For ground-state mode-locked lasers [7,8], the peak power is typically in the range from mW to W. Compared with them, the peak power achieved for our ES mode-locked lasers is comparable to those of conventional mode-locked QD lasers. To understand the chirp in the mode-locked pulses and to determine its sign, the pulses were compressed by a double-grating pulse compressor [36] and then measured by an autocorrelator.…”
Section: Autocorrelation Traces and Two-dimensional Mapping Of Pulsewmentioning
confidence: 76%
“…Several studies have shown [4][5][6], both the ground and the excited-state transitions have subpicosecond gain and absorption recovery time. With the fast carrier dynamics and inherent broadband gain, QDs have been extensively used for modelocked lasers to generate ultra-short pulses [7][8][9][10]. While most of the works were focused on the ground-state transition, some experimental results have indicated that using the excitedstate transition for mode-locking operation may have the potential for achieving shorter and chirpless pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐repetition‐rate (<2 GHz) mode‐locked semiconductor lasers are useful for RF photonics, photonic‐assisted analogue‐to‐digital converters, and other applications in which the combination of affordable low‐speed electronics and ultrafast optics can be leveraged [27, 28]. Owing to the relatively low‐threshold current and internal absorption loss, the QD external cavity mode‐locked lasers become feasible at low‐repetition rates below 10 GHz, corresponding to long laser cavity lengths, in contrast to in bulk/quantum well (QW) lasers [12].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%